2013
DOI: 10.1371/journal.pone.0081571
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-Deep Pyrosequencing of Partial Surface Protein Genes from Infectious Salmon Anaemia Virus (ISAV) Suggest Novel Mechanisms Involved in Transition to Virulence

Abstract: Uncultivable HPR0 strains of infectious salmon anaemia viruses (ISAVs) infecting gills are non-virulent putative precursors of virulent ISAVs (vISAVs) causing systemic disease in farmed Atlantic salmon (Salmo salar). The transition to virulence involves two molecular events, a deletion in the highly polymorphic region (HPR) of the hemagglutinin-esterase (HE) gene and a Q266→L266 substitution or insertion next to the putative cleavage site (R267) in the fusion protein (F). We have performed ultra-deep pyroseque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 64 publications
0
16
0
Order By: Relevance
“…Recently, ISAV quasispecies were demonstrated in farmed Atlantic salmon [53]. The authors identified low-frequency HPR-deleted variants in HPR0-positive screening samples from healthy fish as well as lowfrequency HPR0 variants in subsequent HPR-deleted samples from ISA diseased fish [53]. Similar findings of low-frequency HPAIV in LPAIV and vice versa have been documented in samples from a natural outbreak of AI [40].…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Recently, ISAV quasispecies were demonstrated in farmed Atlantic salmon [53]. The authors identified low-frequency HPR-deleted variants in HPR0-positive screening samples from healthy fish as well as lowfrequency HPR0 variants in subsequent HPR-deleted samples from ISA diseased fish [53]. Similar findings of low-frequency HPAIV in LPAIV and vice versa have been documented in samples from a natural outbreak of AI [40].…”
Section: Discussionmentioning
confidence: 54%
“…RNA viruses are characterized by a high mutation rate and rapid evolutionary potential because of the intrinsic error-prone nature of virus RNA polymerases generating viral quasispecies to maximize diversity and adaptability [51,52]. Recently, ISAV quasispecies were demonstrated in farmed Atlantic salmon [53]. The authors identified low-frequency HPR-deleted variants in HPR0-positive screening samples from healthy fish as well as lowfrequency HPR0 variants in subsequent HPR-deleted samples from ISA diseased fish [53].…”
Section: Discussionmentioning
confidence: 99%
“…; Markussen et al . , ). In addition, a mutation within genomic segment 5, coding for the fusion protein, in all virulent strains has also been suggested as a possible virulence marker (Markussen et al .…”
Section: Introductionmentioning
confidence: 99%
“…ISAV, as an RNA virus lacking polymerase proof reading capability, is prone to genetic shift and drift, and as a segmented genome is also capable of re‐assortment (Markussen et al., ). Consequently, ISAV exists as a number of different genotypes, the HPR0 grouping of which is thought to be both non‐virulent and a putative progenitor of virulent forms (Cook‐Versloot, Griffiths, Cusack, McGeachy, & Ritchie, ; Godoy et al., ).…”
Section: Discussionmentioning
confidence: 99%